Functional characterisation of components in two Plasmodium falciparum Cullin-RING-Ligase complexes - Danushka Marapana; Simon A. Cobbold; Michal Pasternak; Gerald J. Shami; Stuart A. Ralph; Sash Lopaticki; Jumana Yousef; Vineet Vaibhav; Laura F. Dagley; David Komander; Alan F. Cowman (Scientific Reports)
Abstract Ubiquitination is the key eukaryotic post-translational modification that governs protein degradation, localisation, and activity which is mediated by a concerted enzyme cascade. The largest superfamily of these enzymes include the Cullin-RING-Ligase (CRL) complexes. Plasmodium falciparum, the causative agent of the most severe form of malaria in humans, encodes the critical proteins required for ubiquitination, but we do not yet understand the function of this pathway. Here the P. falciparum CRL complexes were characterised to reveal an essential but minimal repertoire controlled by two Cullin scaffolds. A PfCullin1-linked CRL complex, recruiting a single substrate receptor, was identified as being required for parasite inner-membrane biogenesis and DNA replication. A second CRL complex functioning through a PfCullin4 scaffold was identified that utilised a previously unidentified adaptor protein and receptors to support DNA replication. These results show that the P. falciparum CRL complexes are essential in both nuclear maintenance and membrane integrity.